Disharmonisasi Kuhap Baru dan KUHP 2023: Analisis Pasal-Pasal Krusial dan Ancaman terhadap Kepastian Hukum (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the renewal of the Criminal Procedure Code (KUHAP) Baru as an effort to synchronize with the Criminal Code (KUHP) 2023, as well as analyzing crucial articles that potentially cause legal uncertainty in the criminal justice process in Indonesia. Using a juridical-normative method with a descriptive-analytical approach, this research analyzes secondary data from primary, secondary, and tertiary legal materials. The results show that KUHAP Baru successfully addresses some of the mismatches with KUHP 2023 through regulations on alternative punishments, corporate accountability, and protection for vulnerable groups, but still faces conceptual and technical challenges such as legislative disharmony and minimal public participation. On the other hand, crucial articles such as Articles 5, 16, 74, 90, 93, 105, 112A, 124, 132A, and 137A pose risks of legal uncertainty due to the expansion of law enforcement authority without adequate oversight, which can violate the due process principle and human rights. The study's conclusion emphasizes the need for further revisions to strengthen legal certainty and harmonize the criminal justice system.